HUBUNGAN KECEPATAN DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA PUTRA KELAS XI TSM I SMK N 5 PEKANBARU - Ibrahim Ibrahim; Saripin Saripin; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem of this research is the weakness of the student’s long jump result at second grade of TSM 1 SMKN 5 Pekanbaru. The cause of this condition is the student’s weakness in sprint. The purpose of this research is to find the relationship between sprint and the student’s long jump result of the second grade students at TSM 1 SMKN 5 Pekanabaru. The population is boys’ entire student of second grade TSM 1 SMKN 5 Pekanbaru. The sample of this research is 28 boys’ students of TSM 1 SMKN 5 Pekanbaru. The data was analyzed by using correlatin product moment. Besaides the result of data, there is a significant relationship between spreint 50 meters and the students long jump result. it shown by the value of rhitung is 0.651 more than rtable is 0.381.Keywords: Sprint, Long Jump Result